The Influence of Government Expenditure, Investment and Education Level on Employment Opportunities and Community Welfare - Ni Putu Intan Primandani; Ida Bagus Putu Purbadharmaja (International Journal of Social Science and Business, 2023)
Economic development is essentially a process of constant social or systemic improvement aimed at a better quality of life. Economic development affected by several factor including government spending, investment, and level of education on employment opportunities and people's welfare. The purpose of this research is to analyze the effect of government spending, investment, and level of education on employment opportunities and people's welfare. This research originates from secondary data. This research was conducted through non-participant observation in BPS publications. The analysis technique used is path analysis or path analysis. Based on the analysis, it was found that government expenditure, investment, and level of education had a positive and significant effect on district/city employment opportunities. Investment does not have a significant effect, while the level of education and employment opportunities have a positive and significant effect on the welfare of the district/city community. Government spending, investment, and level of education have an indirect effect on people's welfare through employment opportunities. Regional governments in development policies are expected to pay attention to the equitable allocation of government spending and investment and improve programs in the education sector in order to produce quality resources to achieve prosperity.